Participation in Community Walking Following Stroke: The Influence of Self-Perceived Environmental Barriers - Robinson, Cynthia A.; Matsuda, Patricia Noritake; Ciol, Marcia A.; Shumway-Cook, Anne (Physical therapy, 2013)
Community walking is limited among survivors of stroke; however, the contributing factors are not clearly understood. This study examined the association of features in the environment with frequency of community walking following stroke. An observational study design was used, with frequency of community walking data collected prospectively. Thirty survivors of stroke (mean age=67 years; mean months since stroke=40), and 30 older adults without stroke (mean age=68 years) participated. Frequency of community walking (number of trips, walking-related activities [WRA], and the ratio of WRA to trips) and satisfaction were measured using self-report. The Environmental Analysis of Mobility Questionnaire (EAMQ) was used to determine frequency of encounter with versus avoidance of environmental features during community walking. Negative binomial and linear regression models were used to analyze the association of environmental features with measures of community walking. Survivors of stroke reported reduced community walking and fewer encounters with and greater avoidance of features within 8 dimensions of the environment compared with a control group of adults without stroke. Following stroke, avoidance of features in some environmental dimensions was associated with frequency of community walking as measured by number of trips, number of WRA, and the ratio of WRA to trips. Environmental features explained little of the variability in community walking. Limitations included a small sample size and limited diversity among participants. This study examined only physical features in the environment and did not include other environmental factors, such as social support, which may influence participation. Avoidance of features within some, but not all, environmental dimensions was associated with self-reported frequency of community walking following stroke, suggesting that some environmental features may limit community walking more than others.